Rare Presentation of Disseminated Gout Nodulosis and Chronic Inflammatory Arthritis - Sami, Faria; Sami, Shahzad Ahmed; Arora, Shilpa (Case Reports in Rheumatology, 2023)
Background. Gout is an inflammatory arthritis caused by monosodium urate (MSU) deposition. Acute gout is a dramatic painful swelling of the joint; however, MSU can deposit in other tissues as well, including skin, gastrointestinal tract, and bones over time. Disseminated tophi in the skin are a rare presentation of gout known as gout nodulosis. We present a case of gout nodulosis with subcutaneous diffuse miliary nodules in nonarticular areas with concurrent findings suggestive of chronic inflammatory arthritis. Case Presentation. A 39-year-old patient presented with intermittent painful swelling in multiple joints with prolonged morning stiffness. On exam, synovitis was present in multiple proximal interphalangeal joints, wrists, elbows, and knees. Chronic raised pearly nodular rash and swellings on extensor aspects of arms, legs, and anterior abdomen were noticeable. He had negative rheumatoid factor and anti-CCP antibody, C-reactive protein of 0.23 mg/dL, erythrocyte sedimentation rate of 37 mm/hr, and uric acid of 10.6 mg/dL. Hand X-rays revealed severe periarticular osteopenia and joint space narrowing in several joints. Musculoskeletal ultrasound showed a double contour sign at multiple joints and a tophaceous deposit over the olecranon fossa. The biopsy of the nodular rash was consistent with tophi. He was diagnosed with chronic tophaceous gout with skin nodulosis and possible overlap of seronegative rheumatoid arthritis given his X-ray findings. Conclusion. This case discusses one of the rare presentations of gout with disseminated gouty tophi in the skin to raise clinical awareness. The clinical dilemma of the overlap of gout and rheumatoid arthritis posing a diagnostic challenge for clinicians is also highlighted.